2011
DOI: 10.3389/fnagi.2011.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Sensory and Semantic Components on Audio–Visual Speech Perception in Older Adults

Abstract: Previous studies have found that perception in older people benefits from multisensory over unisensory information. As normal speech recognition is affected by both the auditory input and the visual lip movements of the speaker, we investigated the efficiency of audio and visual integration in an older population by manipulating the relative reliability of the auditory and visual information in speech. We also investigated the role of the semantic context of the sentence to assess whether audio–visual integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 68 publications
1
30
0
1
Order By: Relevance
“…Audio-visual congruent targets were identified and located faster and more accurately than both incongruent (i.e., AntVtINC or AtVntINC) targets except in the localisation task where re sponse times to incongruent visual targets paired with an auditory non-target (AntV t^c ) were comparable to spatially congruent audio-visual (AtVtCON) targets again showing how visual input dominated in the object localisation task. Suprathreshold stimuli were used in the current study as a number of studies have shown that older adults demonstrate no audio-visual enhancement in tasks using semantic audio-visual stimuli where the visual and auditory components are degraded (Gordon and Allen, 2009;Maguinness et al, 2011), however, reducing the reliability of the visual stimuli may have reduced visual dominance effects found in the current study. We failed to find evidence in either the accuracy or response time data for a three-way interaction between the age group of the participants, the task they performed and the modality in which the target was presented.…”
Section: Atvtc0nmentioning
confidence: 89%
See 2 more Smart Citations
“…Audio-visual congruent targets were identified and located faster and more accurately than both incongruent (i.e., AntVtINC or AtVntINC) targets except in the localisation task where re sponse times to incongruent visual targets paired with an auditory non-target (AntV t^c ) were comparable to spatially congruent audio-visual (AtVtCON) targets again showing how visual input dominated in the object localisation task. Suprathreshold stimuli were used in the current study as a number of studies have shown that older adults demonstrate no audio-visual enhancement in tasks using semantic audio-visual stimuli where the visual and auditory components are degraded (Gordon and Allen, 2009;Maguinness et al, 2011), however, reducing the reliability of the visual stimuli may have reduced visual dominance effects found in the current study. We failed to find evidence in either the accuracy or response time data for a three-way interaction between the age group of the participants, the task they performed and the modality in which the target was presented.…”
Section: Atvtc0nmentioning
confidence: 89%
“…However, Gordon and Allen (2009) found that older adult's performance on a speech task was not enhanced relative to younger adults when visual cues were blurred and audio speech was presented in noise. In addition, Maguinness et al (2011) reported relatively worse recall by older adults for semantically meaningless audio-visual speech, particularly when visual cues were blurred relative to non-blurred visual cues. These find ings are in contrast to what would be predicted by the principle of inverse effectiveness (Meredith and Stein, 1983) whereby multisensory enhancement is more pronounced when individual sensory inputs are less effective.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Greater WMC was associated with a lower (more noisy) SNR at which maximal gain was observed. Given the known decreases in WMC with age, these results provide strong evidence that cognitive decline, specifically declines in working memory, may influence task performance that is generally considered more sensory based – though it should be noted that perceptual and cognitive declines do not occur in isolation, and likely interact [96-98]. …”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of noise can be tolerated when the semantic content of speech is predictable (Pichora-Fuller, 2008). Indeed when older adults cannot rely on the semantic predictability of a sentence, for example, because the sentence does not express a meaningful content, they benefit more from the addition of visual information to auditory speech than younger adults (Maguinness et al, 2011). …”
Section: Introductionmentioning
confidence: 99%